If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 41 + -6x = 1 + -7x + 4 Reorder the terms: 41 + 5x + -6x = 1 + -7x + 4 Combine like terms: 5x + -6x = -1x 41 + -1x = 1 + -7x + 4 Reorder the terms: 41 + -1x = 1 + 4 + -7x Combine like terms: 1 + 4 = 5 41 + -1x = 5 + -7x Solving 41 + -1x = 5 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 41 + -1x + 7x = 5 + -7x + 7x Combine like terms: -1x + 7x = 6x 41 + 6x = 5 + -7x + 7x Combine like terms: -7x + 7x = 0 41 + 6x = 5 + 0 41 + 6x = 5 Add '-41' to each side of the equation. 41 + -41 + 6x = 5 + -41 Combine like terms: 41 + -41 = 0 0 + 6x = 5 + -41 6x = 5 + -41 Combine like terms: 5 + -41 = -36 6x = -36 Divide each side by '6'. x = -6 Simplifying x = -6
| 56.08+57.98= | | 96=+4(6x-6) | | 2-5r+2r^2=0 | | 2x^2+6+2x=0 | | 32c+3=15+26c | | 10y-7y-7=47.57 | | 0.6x-0.3(3)=4.5 | | X^3-2x^2-19x+20=5 | | U+7=11 | | q^2+2q=-1 | | 3x^2+49+77=0 | | 8(w-7)=5w-29 | | 3x-5(3-x)=7x+21-5+x | | 5x+6=4(x-2) | | 7(e-8)=98 | | 3(x+7)+6(2x+3)=69 | | 4v-2=5v-6 | | 3x-7x=37 | | 2y-12=12-2p | | 2u=12 | | 2x^4+16x^3+32x^3=0 | | x^2-8x-14=0 | | x^3+8x+14=0 | | (w+3)7=-7 | | 0=x^2-14x+49 | | 13=m | | 3(x-2)=12x | | 9y-8-5y=5y-5 | | [3t-2]+6=2 | | -9+5x+2=48 | | 1.5t=-9 | | 8=12y+6x |